Food Taboos and Prevention of Postpartum Anemia in the Karo Ethnic Community - Desideria Yosepha Ginting; Nur Indrawati Lipoeto; Adang Bachtiar; Joserizal Serudji (Indonesian Journal of Global Health Research, 2025)
Postpartum anemia is a condition characterized by reduced hemoglobin levels in the blood, which diminishes the blood’s ability to optimally transport oxygen to meet the body’s physiological needs. Although a global health issue, this condition remains frequently overlooked and under-researched. This study aims to explore the perceptions, meanings, and values associated with cultural practices, such as food taboos, and their relationship to the occurrence of postpartum anemia in the Karo ethnic community. Using a qualitative approach, data were gathered through in-depth interviews with three postpartum mothers. The interviews were conducted over multiple sessions with each participant until responses became consistent. The findings revealed that specific food taboos are practiced during the postpartum period, which are culturally significant but may affect iron intake and risk worsening anemia. Postpartum mothers in the Karo ethnic community avoid consuming seafood and leafy vegetables with hairy surfaces. These foods are restricted due to the belief that they may cause itching. Food taboos among postpartum mothers in the Karo ethnic community can lead to micronutrient deficiencies, contributing to anemia. This highlights the need for health interventions that integrate cultural context and local wisdom.